Correction: A ditopic calix[4]pyrrole amide derivative: highlighting the importance of fundamental studies and the use of NaPh4B as additive in the design and applications of mercury(ii) ion selective electrodes. Issue 25 (7th July 2015) - Danil de Namor, Angela F.; Gamouz, Abdelaziz El; Alharthi, Salman; Hakawati, Nawal Al; Varcoe, John R.
<x xml:space="preserve">Abstract</x> Correction for 'A ditopic calix[4]pyrrole amide derivative: highlighting the importance of fundamental studies and the use of NaPh4B as additive in the design and applications of mercury(ii) ion selective electrodes' by Angela F. Danil de Namor et al., J. Mater. Chem. A, 2015, DOI: 10.1039/c5ta02215k.